PENGEMBANGAN PROFESIONAL UNTUK GURU: MENUJU GURU SEBAGAI PEMBELAJAR - Irwandi, Irwandi (Pelita Bangsa Pelestari Pancasila, 2017)
In the 21th century, education system internationally strives to raise the pursuit of excellence at all levels. Perhaps understandably, any efforts to improve education quality cannot succeed without the continuous support and cooperation of a professional teacher. This fact is widely recognized in international attention mostly in term of promoting the continuing professional of teachers. The term of ‘continuing’ refers to the need for ongoing development of teachers’ knowledge, professional skill, and their effectiveness in schools. This is a reaction to the professional development which is not satisfied yet in leading to an increase in teacher knowledge, skills, and commitment. This paper explores the concept of continuing professional development, the limitation of current approaches to professional development, and the reinvigoration strategy of teacher professional development. The concern is on teachers rather than school leaders, but the implications are highlighted for school leadership and management.